Organizational Innovation and Service Delivery in Public Universities in Western Region, Kenya - Ruth Mandila; Jackline Akoth Odero; Gerald Maniagi Musiega (Journal of Business and Social Review in Emerging Economies)
Purpose: Organizational innovation is acknowledged as a key factor in assisting public universities maintain service delivery efficiency. Public universities operate in a dynamic and competitive business environment that poses strategic, operational and tactical challenges which affect their service delivery efficiency. This study sought to establish the effect of organizational innovation on service delivery in public universities in Western region.